Efeito do extrato de pimenta rosa e do tipo de embalagem sobre a qualidade e estabilidade oxidativa de hambúrguer de frango - Diniz, Julia Pereira (Universidade Federal de São Carlos, 2022)
For years, pink pepper has been used in folk medicine as an analgesic and anti-inflammatory, which has aroused the interest of the scientific community regarding its biological activities, such as antioxidant. The search for natural compounds as alternatives to the use of synthetic antioxidants has been growing in the meat industry. Among meat products, processed chicken products have a great need to use these additives, as they have a high susceptibility to the development of lipid oxidation. This study aimed to evaluate the effect of pink pepper extract and the type of packaging (aerobic and vacuum) on the physicochemical characteristics and oxidative stability of chicken burgers. Pink pepper ethanol extracts were obtained and analyzed for total phenolic compounds and antioxidant activity (DPPH and ABTS). Subsequently, the extracts at a concentration of 90 mg of gallic acid equivalent/kg of meat were applied to chicken hamburgers and evaluated as a natural antioxidant compared to a formulation containing synthetic antioxidant (BHT), and a control formulation (without antioxidants). All samples were stored in an aerobic environment and under vacuum for seven days at 4 °C and evaluated for oxidative stability, color and pH. The pink pepper extract showed considerable content of phenolic compounds and antioxidant activity. The hamburger with pink pepper extract was more effective than the one with BHT to delay the lipid oxidation of samples conditioned in an aerobic environment and was as efficient as this synthetic antioxidant in samples packed under vacuum. Regarding the samples packaged in an aerobic environment, pink pepper proved to be as efficient as BHT after 7 days of storage. There was a slight reduction in pH of the samples packed in an aerobic environment and darkening of the samples with the addition of pink pepper extract, probably due to the slightly acidic pH and the coloring of the natural extract. The application of pink pepper extract as a natural antioxidant is efficient to delay lipid oxidation, showing that it can be used as a promising natural antioxidant in the industry.
Effect of pink pepper extract and type of packaging on the quality and oxidative stability of chicken burger
Keywords: Antioxidantes naturais; Schinus terebinthifolius; Embalagem a vácuo; Oxidação lipídica; Compostos fenólicos; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::ENGENHARIA DE ALIMENTOS::ARMAZENAMENTO DE ALIMENTOS; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::TECNOLOGIA DE ALIMENTOS::EMBALAGENS DE PRODUTOS ALIMENTARES; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::TECNOLOGIA DE ALIMENTOS::TECNOLOGIA DE PRODUTOS DE ORIGEM ANIMAL